Histone Modifications Define Expression Bias of Homoeologous Genomes in Allotetraploid Cotton . Issue 3 (16th September 2016) - Zheng, Dewei; Ye, Wenxue; Song, Qingxin; Han, Fangpu; Zhang, Tianzhen; Chen, Z. Jeffrey
Abstract : Comparative analysis of immunostained metaphase chromosomes at the single cell level with ChIP-seq of individual genes reveals a chromatin basis for biased homoeolog gene expression in polyploids. Abstract: Histone modifications regulate gene expression in eukaryotes, but their roles in gene expression changes in interspecific hybrids or allotetraploids are poorly understood. Histone modifications can be mapped by immunostaining of metaphase chromosomes at the single cell level and/or by chromatin immunoprecipitation-sequencing (ChIP-seq ) for analyzing individual genes. Here, we comparatively analyzed immunostained metaphase chromosomes and ChIP-seq of individual genes, which revealed a chromatin basis for biased homoeologous gene expression in polyploids. We examined H3K4me3 density and transcriptome maps in root-tip cells of allotetraploid cotton ( Gossypium hirsutum ). The overall H3K4me3 levels were relatively equal between A and D chromosomes, which were consistent with equal numbers of expressed genes between the two subgenomes. However, intensities per chromosomal area were nearly twice as high in the D homeologs as in the A homeologs. Consistent with the cytological observation, ChIP-seq analysis showed that more D homeologs with biased H3K4me3 levels than A homeologs with biased modifications correlated with the greater number of the genes with D-biased expression than that with A-biased expression in most homeologous chromosome pairs. Two chromosomes displayed different expression levels compared with other chromosomes, which correlate with known translocations and may affect the local chromatin structure and expression levels for the genes involved. This example of genome-wide histone modifications that determine expression bias of homeologous genes in allopolyploids provides a molecular basis for the evolution and domestication of polyploid species, including many important crops.